2014
DOI: 10.2147/cia.s68145
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and efficacy of cognitive telerehabilitation in early Alzheimer’s disease: a pilot study

Abstract: BackgroundThis pilot study compared the effects of lexical-semantic stimulation through telecommunication technology (LSS-tele) with in-person LSS (LSS-direct) and unstructured cognitive treatment (UCS) in patients with early Alzheimer’s disease.MethodsTwenty-seven patients with Alzheimer’s disease in the very early stage (Mini-Mental State Examination [MMSE] >26/30) were divided into three groups: seven patients received LSS-tele treatment, ten received standard LSS-direct intervention, and ten participants u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 33 publications
0
61
0
2
Order By: Relevance
“…42 With regard to results, four studies 21 , 22 , 39 , 41 showed post-intervention improvement in naming skills (EL I, II and III) 21 , 22 , 39 , 41 and phonemic, verbal and semantic fluency (EL I). 39 , 40 Only one study (classified as EL IV) 42 showed no post-intervention effects, with few and insignificant changes from baseline for naming skills and vocabulary. 42 Only two studies investigated the maintenance of positive effects in follow-ups after intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…42 With regard to results, four studies 21 , 22 , 39 , 41 showed post-intervention improvement in naming skills (EL I, II and III) 21 , 22 , 39 , 41 and phonemic, verbal and semantic fluency (EL I). 39 , 40 Only one study (classified as EL IV) 42 showed no post-intervention effects, with few and insignificant changes from baseline for naming skills and vocabulary. 42 Only two studies investigated the maintenance of positive effects in follow-ups after intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that were classified into this category used activities such as tasks which requested the patient to detect semantic relationships between items, name figures, interpret the meaning of isolated words, as well as words within sentences and within stories. From the six studies included in this category, two were classified as EL I, 39 , 40 one as EL II, 41 two as EL III 21 , 22 and one as EL IV. 42 With regard to results, four studies 21 , 22 , 39 , 41 showed post-intervention improvement in naming skills (EL I, II and III) 21 , 22 , 39 , 41 and phonemic, verbal and semantic fluency (EL I).…”
Section: Resultsmentioning
confidence: 99%
“…Besides the diagnostic evaluation and follow-up monitoring, telemedicine interventions for dementia include internet-based information and support groups, robotic companions, the use of smartphones to report symptoms (258, 363, 364), and cognitive rehabilitation training (365).…”
Section: Telemedicinementioning
confidence: 99%
“…The advances in ICT have triggered a wide use of TR solutions in different domains. Nowadays, we can find solutions for the treatment of different physical (Piron et al, 2004 ; Sandlund et al, 2011 ) and cognitive diseases (Gervasi et al, 2010 ; Jelcic et al, 2014 ; Levin et al, 2015 ) and others that aim at providing more comprehensive solutions (Simmons et al, 2014 ; Oliver et al, 2016 ; Cameirao et al, 2017 ; Teruel et al, 2017a ). As stated in Lange et al ( 2012 ), there are some important features that should be considered in the design of RT tasks: they should be adjustable in terms of difficulty level; capable of repetitive and hierarchical administration; quantifiable to measure performance and progress; relevant to the real world; capable of providing users with strategic feedback; and capable of motivating the user’s engagement.…”
Section: Rehabilitation and Technologymentioning
confidence: 99%